Communicative competence formation of future economists: axiological approach - Семеног, Олена Миколаївна (Pedagogy of Higher and Secondary Education, 2013)
Semenog O. M. Communicative competence formation of future economists: axiological approach. On the bases of modern approaches, including axiological approach in the article is described communicative competence of the economist. As a result of research are designed evaluation cards of communicative competence formation. Also are tested methods (methods of «brainstorming», business role games) that promotes qualitative communicative competence formation of future economists in high educational economic institution.